2007
DOI: 10.1016/j.compositesa.2006.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Mode I interlaminar fracture behavior and mechanical properties of CFRPs with nanoclay-filled epoxy matrix

Abstract: The Mechanical properties and fracture behavior of nanocomposites and carbon fiber composites (CFRPs) containing organoclay in the epoxy matrix have been investigated. Morphological studies using TEM and XRD revealed that the clay particles within the epoxy resin were intercalated or orderly exfoliated. The organoclay brought about a significant improvement in flexural modulus, especially in the first few wt% of loading, and the improvement of flexural modulus was at the expense of a reduction in flexural stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
5
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(153 citation statements)
references
References 19 publications
6
141
5
1
Order By: Relevance
“…Both materials exhibited a distinctively smooth top layer after UV exposure, suggesting brittle fracture caused by UV embrittlement with limited plastic deformation. The bulk of the materials displayed rough surface, resembling the fracture surfaces of both materials studied previously [15]. The smooth top layer was absent in the specimens without UV exposure, partly confirming our assumption that its thickness is a measure of the degradation due to UV radicals.…”
Section: Fracture Surface Morphologies Of Uv-exposed Tensile Specimenssupporting
confidence: 70%
“…Both materials exhibited a distinctively smooth top layer after UV exposure, suggesting brittle fracture caused by UV embrittlement with limited plastic deformation. The bulk of the materials displayed rough surface, resembling the fracture surfaces of both materials studied previously [15]. The smooth top layer was absent in the specimens without UV exposure, partly confirming our assumption that its thickness is a measure of the degradation due to UV radicals.…”
Section: Fracture Surface Morphologies Of Uv-exposed Tensile Specimenssupporting
confidence: 70%
“…At higher CNT contents (0.25-0.5 wt%, Fig. 9(c) and (d)), these river markings became shorter and round-ended, similar to those observed in nanocomposites reinforced with high contents of nanoclay particles [15]. It appears that the increasing number of river markings roughly corresponds to the number of isolated, well-dispersed CNTs, which forced the cracks to propagate bypassing the CNTs and taking a long path.…”
Section: Fracture Resistance Of Nanocompositesmentioning
confidence: 64%
“…The absence of basal reflection in nanocomposites indicates good exfoliation of silicate platelets in epoxy matrix. The formation of exfoliation or intercalation of silicate platelets is due to the reaction of OMMT with amine hardener [13]. Ratna et al [14] also reported that the absence of d 100 peak in the X-ray spectrum of all binary and ternary epoxy/layered silicate systems indicates exfoliation of clay.…”
Section: Sample Characterizationmentioning
confidence: 99%